Stroke volume and stroke volume variation, but not cardiac index is associated with survival of majorly burned patients in early burn shock - Kruse, Marianne; Plettig, Philip; Josuttis, David; Guembel, Denis; Guethoff, Claas; Hartmann, Bernd; Kuepper, Simon; Gebhardt, Volker; Schmittner, Marc (Journal of intensive care medicine, 2025)
Adequate fluid therapy is crucial to maintain organ function after burn trauma. Major burns lead to a systemic response with fluid loss and cardiac dysfunction. To guide fluid therapy, measurement of cardiac pre- and afterload is helpful. Whereas cardiac function is usually measured after admission to intensive care unit (ICU), in this study, hemodynamic monitoring was performed directly after arrival at hospital. We conducted a prospective cohort study with inclusion of 19 patients (male/female 13/6, 55 ± 18 years, mean total body surface area 36 ± 19%). Arterial waveform analysis (PulsioFlexProAqt®, Getinge) was implemented immediately after admission to hospital to measure cardiac pre- and afterload and to guide resuscitation therapy. Cardiac parameters 3.75 (2.67-6.0) h after trauma were normal regarding cardiac index (3.45 ± 0.82) L/min/m², systemic vascular resistance index (1749 ± 533) dyn sec/cm5 m2, and stroke volume (SV; 80 ± 20) mL. Stroke volume variation (SVV) was increased (21 ± 7) % and associated with mortality (mean SVV survivors vs nonsurvivors 18.92 (±6.37) % vs 27.6 (±5.68) %, P = .017). Stroke volume was associated with mortality at the time of ICU-admission (mean SV survivors vs nonsurvivors 90 (±20) mL vs 50 (±0) mL, P = .004). Changes after volume challenge were significant for SVV (24 ± 9 vs19 ± 8%, P = .01) and SV (68 ± 24 vs 76 ± 26 mL, P = .03). We described association of SVV and SV with survival of severely burned patients in an observational study. This indicates high valence of those parameters in the early postburn period. The use of an autocalibrated device enables a very early monitoring of parameters relevant to burn shock survival.